Antimicrobial Resistance in Agri-Food Chain and Companion Animals as a Re-emerging Menace in Post-COVID Epoch: Low-and Middle-Income Countries Perspective and Mitigation Strategies - Bandyopadhyay, Samiran; Samanta, Indranil (Frontiers in Veterinary Science, 2020)
Antimicrobial resistance (AMR) leads to enormous financial losses from issues such as high morbidity, mortality, man-days lost, hospital length of stay, health-care, and social costs. In humans, over prescription of antimicrobials, which is presumably higher during COVID, has been identified as the major source of selection for antimicrobial resistant bacteria; however, use of antimicrobials in food and companion animals, fish, and vegetables, and the environmental resistance gene pool, also play important roles. The possibilities of unnecessary use of antibiotics as prophylaxis during and after COVID in livestock and companion animals exist in low-and middle-income countries. A considerable loss in gross domestic product (GDP) is also projected in low-and middle-income countries (LMICs) due to AMR by the year 2050, which is further going to be reduced due to economic slowdown in the post-COVID period. Veterinary hospitals dedicated to pets have cropped up, especially in urban areas of LMICs where use of antimicrobials has also been increased substantially. The inevitable preventive habit built up during COVID with the frequent use of hand sanitizer might trigger AMR due to the presence of cross-resistance with disinfectants. In LMICs, due to the rising demand for animal protein, industrial food animal production (IFAP) is slowly replacing the small-scale backyard farming system. The lack of stringent regulations and monitoring increased the non-therapeutic use of antimicrobials in industrial farms where the persistence of antimicrobial resistant bacteria has been associated with several factors other than antimicrobial use, such as co-resistance, cross-resistance, bacterial fitness, mixing of new and old animals, and vectors or reservoirs of bacterial infection. The present review describes types of antimicrobials used in agri-food chains and companion animals in LMICs with identification of the gap in data, updated categories of prevalent antimicrobial resistant bacteria, the role of animal farms as reservoirs of resistant bacteria, and mitigation strategies, with a special focus on the pivotal strategy needed in the post-COVID period.